PELAKSANAAN OPERASIONAL SISTEM INFORMASI PERSEDIAAN PADA PT ELANG PERKASA LESTARI JAYA - Nyoman Sukawati, Anak Agung; Widjaya, Ivanna Handayani; Uly, Alexander; Heni, Heni (Bina Nusantara University, 2009)
The purpose of this study is to determine the extent to which the operational performance of information systems for inventory based on user perceptions of information systems. The research method used is survey method, descriptive techniques, and capture data using a questionnaire and before use, calibrated test item validity and reliability test. The technical data analysis used a range of criteria and methods of Pearson (Product Moment), and data processing with the help of SPSS version 12.0, and Microsoft Excel. The results of this study the overall average of 14.48 on a scale indicator from 10.6 to 15.0, where the network operating indicators, preparation and data entry, and production control showed less good. The conclusion shows that the perception of users on information systems for inventory runs poorly.Keywords: operational implementation, inventory information system, range criterion method, Pearson correlation method